Product Market Competition and Managerial Disclosure of Earnings Forecasts: Evidence from Import Tariff Rate Reductions - Huang, Ying; Jennings, Ross; Yu, Yong (The Accounting Review, 2017)
ABSTRACT This study examines the effect of product market competition on managerial disclosure of earnings forecasts using large reductions in U.S. import tariff rates to identify an exogenous increase in competition for domestic firms in U.S. product markets. Our difference-in-differences estimations show that tariff reductions are associated with a significant decrease in management forecasts of annual earnings by U.S. domestic firms. Further, this decrease is more pronounced when the tariff rate reduction triggers a greater increase in imports and when the forecasts are likely to incur higher proprietary costs. Our findings are consistent with competition from existing rivals reducing voluntary disclosure through increased proprietary costs.